The Swiss Model of Direct Democracy - Matyja, Miroslaw (Technium Social Sciences Journal, 2019)
Due to the challenges that modern representative democracy is facing, citizens and politicians of various countries are looking for new solutions and ways to ensure the optimal functioning of their political and decision making system. In this context, Switzerland appears to be a country relatively immune to the current crisis. Why is that? As a direct democracy where the rule of the people remains the fundamental principle, it provides its citizens with instruments: referendum, popular initiative, popular veto, which allow them to resolve any problems that arise both on the national and local level. The essential characteristic of the Swiss system, which is also its main strength, is that unlike other European democracies it grants its citizens full power over their homeland, making them the actual sovereign. The author of this article discusses various aspects of the Swiss model of democracy and suggests that it offers the best solutions for the optimal development of any country.